Peningkatan keterampilan menulis permulaan melalui pendekatan whole language tipe jurnal writing pada siswa sekolah dasar - Haryanto, Dwi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
The purpose of this research was to improve the learning approaches whole language type journal writing study for the secon grade students of SD Negeri 1 Bangsri in the academic year 2015/2016. This research used classroom action research and was performed in two cycle. Each cycle consisted of four steps, planning, action, observation, and reflection. The subject of this research were 41 students and the teachers. The data sources derived from students and teachers. The data collecting techniques were questionnaire, observation, interview, and documentation. The data validation used triangulation techniques, triangulation sources, and review informant. The data analysis used interactive analysis. The conclusion of this research shows that the application of learning approaches whole language type journal writing study can improve the learning activeness about writing skill for secon grade students in the SD Negeri 1 Bangsri in the academic year 2015/2016.